Incidental Detection of Adult Polysplenia Syndrome With Situs Inversus Totalis, Interrupted Inferior Vena Cava, and Bronchiectasis - Kanupriya Arora; Mansi Verma; Sushma Makhaik (Methodist DeBakey Cardiovascular Journal)
Incidental detection of polysplenia associated with situs inversus totalis in an adult is rarely reported in literature.1,2 “Heterotaxy” refers to a wide spectrum of anomalies involving dysmorphism of thoracoabdominal organs across the right-left axis of the body. Polysplenia is observed in left isomerism along with bilateral bilobed bronchi and bilateral morphologic left atria. However, in this case, polysplenia was present without isomerism.